Road Segment Performance Analysis - Kholidia Ayunaning; Rahmat Dwi Sutrisno; Avisha Gita Prafitasiwi (Kontribusia : Research Dissemination for Community Development, 2023)
Section Jl. Raya Roomo Manyar Gresik is an access for large vehicles to enter and leave the factories around it, not to mention the entry and exit of factory workers during shift changes. With a 2/2UD road, it is not uncommon to make Jl. Raya Roomo Manyar Gresik is one of the congestion centers in the Gresik Regency — evaluation of the performance of the Jl. Raya Roomo Manyar Gresik shows that the Jl. Raya Roomo Manyar Gresik is experiencing saturation obtained from the MKJI 1997 performance analysis method of the road segment, and according to the Ministry of Transportation regulation No.96 of 2015, the Jl. Raya Roomo Manyar Gresik is included in the service level category D with a V/C ratio 0.84.